PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MENITI HIDUP DENGAN KEMULIAAN DI KELAS X IPS 1 SMA NEGERI 4 BUKITTINGGI - Suhana, Suhana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to obtain data and information about the implementation of the Jigsaw method, to improve the learning outcomes of students of class X IPS 1 of SMA 4 in Bukittinggi City. This study uses the method of observation, tests and observation sheets. The results of the observations are then analyzed and used as material for action planning in the next cycle. The data obtained is then processed, in order to draw conclusions. The findings of the data after analysis showed that after the first cycle, 20 students received an average score below the KKM (75). Classically the value is not satisfactory, then the second cycle is done, the value of students has increased with the results of all students have met the KKM value, with an average of 80.58. Overall, the learning outcomes of Islamic Education in the material lead life with glory (self-control, khuznudzan and ukhuwwah) in class X IPS 1, Bukittinggi City 4 High School has increased. The implications of the results of Classroom Action Research (CAR) through the jigsaw learning method approach can improve PAI learning outcomes in class X IPS 1 Bukittinggi City 4 High School.